Ancient letters: classical and late antique epistolography - Morello, Ruth; Ebbeler, Jennifer; Morrison, A. D. ca. 20./21. Jh. (Oxford University Press, 2007)
What is a letter? / Roy K. Gibson and A. D. Morrison -- Down among the documents : criticism and papyrus letters / G. O. Hutchinson -- '...When who should walk into the room but...' : epistoliterarity in Cicero, ad qfr. 3.1 / John Henderson -- Cicero's stomach : political indignation and the use of repeated allusive expressions in Ciceros correspondence / Stanley E. Hoffer -- Didacticism and epistolarity in Horace's epistles 1 / A. D. Morrison -- The importance of form in Seneca's philosophical letters / Brad Inwood -- Letters of recommendation and the rhetoric of praise / Roger Rees -- Confidence, Inuidia, and Pliny's epistolary curriculum / Ruth Morello -- The letter's the thing (in Pliny, book 7) / William Fitzgerald -- The epistula in ancient scientific and technical literature, with special reference to medicine / D. R. Langslow -- Back to Fronto : doctor and patient in his correspondence with an emperor / Annelise Freisenbruch -- Alciphron's epistolarity / Jason Konig -- Better than speech : some advantages of the letter in the Second Sophistic / Owen Hodkinson -- Mixed messages : the play of epistolary codes in two late antique Latin correspondences / Jennifer Ebbeler -- St Patrick and the art of allusion / Andrew Fear